Sports-related concussion (SRC) in road cycling: establishing the RoadsIde heaD injury assEssment (RIDE) for elite road cycling - Heron, N.; Jonathan, E. (British Journal of Sports Medicine, 2021)
Background Despite recent advances in the diagnosis and management of sports-related concussion (SRC) in the sports medicine community; as well as heightened recognition of the condition by the public and media, some sports, such as road cycling, appear to lack effective concussion assessment, diagnosis and management protocols.